2022
DOI: 10.1038/s41467-022-32130-5
|View full text |Cite
|
Sign up to set email alerts
|

Aβ42 oligomers trigger synaptic loss through CAMKK2-AMPK-dependent effectors coordinating mitochondrial fission and mitophagy

Abstract: During the early stages of Alzheimer’s disease (AD) in both mouse models and human patients, soluble forms of Amyloid-β 1–42 oligomers (Aβ42o) trigger loss of excitatory synapses (synaptotoxicity) in cortical and hippocampal pyramidal neurons (PNs) prior to the formation of insoluble amyloid plaques. In a transgenic AD mouse model, we observed a spatially restricted structural remodeling of mitochondria in the apical tufts of CA1 PNs dendrites corresponding to the dendritic domain where the earliest synaptic l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 124 publications
(204 reference statements)
6
54
0
Order By: Relevance
“…Two recent studies are particularly relevant in this regard: The first study ( Bold et al, 2022 ) showed that APPsα (the proteolytic cleavage product of APP along the nonamyloidogenic pathway, i.e., the one not producing Aβ) rescued abnormally low spine density in tauopathy model mice, even when applied at nanomolar concentrations. In contrast, the second study ( Lee et al, 2022 ) as well as many others, showed that soluble forms of oligomeric Aβ (the proteolytic APP cleavage product along the amyloidogenic pathway) drove excitatory synapse loss. Intriguingly, this study provided compelling evidence for causal links between Aβ-triggered loss of postsynaptic specializations (comparable both in extent and time course to Figure 6 above) and an upstream loss of dendritic mitochondria biomass, and by extension, compromised energy production capacity.…”
Section: Discussionmentioning
confidence: 91%
“…Two recent studies are particularly relevant in this regard: The first study ( Bold et al, 2022 ) showed that APPsα (the proteolytic cleavage product of APP along the nonamyloidogenic pathway, i.e., the one not producing Aβ) rescued abnormally low spine density in tauopathy model mice, even when applied at nanomolar concentrations. In contrast, the second study ( Lee et al, 2022 ) as well as many others, showed that soluble forms of oligomeric Aβ (the proteolytic APP cleavage product along the amyloidogenic pathway) drove excitatory synapse loss. Intriguingly, this study provided compelling evidence for causal links between Aβ-triggered loss of postsynaptic specializations (comparable both in extent and time course to Figure 6 above) and an upstream loss of dendritic mitochondria biomass, and by extension, compromised energy production capacity.…”
Section: Discussionmentioning
confidence: 91%
“…A potential confounding factor in the variation observed in the literature regarding mitochondrial length is recent data reporting differential mitochondria morphologies in different brain regions. It is now clear that both distinct neuron types and even the compartments within the same neuron (soma, dendrites, and axon) regulate mitochondria morphology to different levels ( Faits et al, 2016 ; Lewis et al, 2018 ; Chandra et al, 2019 ; Janickova et al, 2020 ; Faitg et al, 2021 ; Lee et al, 2022 ). However, it is unclear if or how these different mitochondrial populations would be affected by the different fixatives and perfusion methods.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a strong correlation between microglial activation and metabolic dysfunction in AD has been demonstrated in both basic research and clinical studies [ 5 , 18 , 19 ]. In AD, a series of mitochondrial abnormalities have been identified, including structure alteration, age-dependent accumulation of mitochondrial DNA (mtDNA) changes, altered mitochondrial membrane potential, excessive mitochondrial ROS production, reduced mitochondrial adenosine triphosphate (ATP), disrupted electron transport chain (ETC), and increased mitochondrial fragmentation, leading to defective mitophagy in microglia and other brain cells [ 13 , 22 29 ]. In addition, chronic exposure to Aβ and p-Tau induces dysregulated expression of late-onset AD-associated genes [ 30 ], mitochondrial toxicity, and metabolic dysfunction in microglia [ 31 ].…”
Section: Introductionmentioning
confidence: 99%